Perpendicular magnetic anisotropy tunnel junction film prepared by magnetic control equipment and preparation method of perpendicular magnetic anisotropy tunnel junction film

By using magnetron devices to prepare a perpendicular magnetic anisotropic magnetic tunnel junction film at Ta/CoFeB/MgO/Ta interface in magnetic memory devices, the problems of low storage density, low magnetization and flip efficiency and large power consumption are solved, and the storage effect of high thermal stability and ultra-low power consumption is achieved.

CN119824365APending Publication Date: 2025-04-15TRUTH EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510025007.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In existing magnetic memory devices, in-plane magnetic anisotropic tunnel junctions have problems such as low storage density, low magnetization and flip efficiency and large power consumption.

Method used

Magnetic tunnel junction film with perpendicular magnetic anisotropy (PMA) of Ta/CoFeB/MgO/Ta interface was prepared by magnetron control equipment. By adjusting the process air pressure, sputtering power and sputtering distance, excellent surface roughness and crystallinity of Ta, CoFeB and MgO films were achieved.

Benefits of technology

Magnetic tunnel junctions with high thermal stability without large aspect ratios are achieved. They are suitable for spintronic information devices with smaller sizes and faster read and write speeds, and have the important significance of ultra-low power consumption storage and computing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824365A_ABST
    Figure CN119824365A_ABST
Patent Text Reader

Abstract

The invention discloses a vertical magnetic anisotropy tunnel junction thin film prepared by magnetic control equipment and a preparation method thereof, and the thin film comprises a silicon oxide wafer, a Ta film is deposited on the surface of the silicon oxide wafer, the Ta film is used as a metal buffer layer, a CoFeB film is deposited on the surface of the Ta film, the CoFeB film is used as a ferromagnetic layer, an MgO film is deposited on the surface of the CoFeB film, and the MgO film is used as a ferromagnetic layer. An MgO film is used as an insulating layer to play a role of an insulating barrier, a Ta film is also deposited on the surface of the MgO film, the Ta film is used as a covering layer to play a role of preventing oxidation, and the invention relates to the technical field of film deposition. According to the vertical magnetic anisotropy tunnel junction thin film prepared by the magnetic control equipment and the preparation method thereof, the surface roughness of Ta, CoFeB and MgO thin films is reduced by adjusting experimental parameters such as process air pressure, sputtering power and sputtering distance, and crystallization of MgO is improved by reducing the process air pressure and increasing the experimental parameters such as sputtering power.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thin film deposition, in particular to a preparation method of a perpendicular magnetic anisotropic tunnel junction thin film by a magnetron device. Background Art

[0002] With the rapid development of information technology, the requirements for storage devices are getting higher and higher. Traditional storage technologies such as hard disks (HDDs) and flash memory (Flash) are gradually facing bottlenecks in terms of storage density, read and write speeds, and energy consumption. MRAM, as an emerging storage technology, is expected to overcome these problems. Magnetic materials play a vital role in modern science and technology. Traditional magnetic material research mainly focuses on in-plane magnetic anisotropy, that is, the easy magnetization axis of the material is in the plane of the film. However, there are two problems with in-plane magnetic anisotropic tunnel junctions. First, such devices usually need to be designed as elliptical or rectangular, which limits the storage density of magnetic random access memory; second, the magnetization switching efficiency is low, resulting in high power consumption. With the demand for device miniaturization and high performance, perpendicular magnetic anisotropy (PMA) materials have gradually attracted attention. In thin film magnetic materials, magnetic anisotropy determines the difficulty and magnetization direction of magnetization. For perpendicular magnetic anisotropic materials, it is easier to achieve a magnetization direction perpendicular to the film plane. This perpendicular magnetization characteristic has huge advantages in magnetic storage and spintronics devices. For example, in magnetic random access memory (MRAM), perpendicular magnetization can achieve higher storage density because stacking memory cells in the vertical direction is more conducive to shrinking device size than expanding them in a plane, and can reduce interference between cells.

[0003] During the research, scientists found that when these materials are combined to form a thin film in the structure of Ta / CoFeB / MgO, they can exhibit perpendicular magnetic anisotropy. From a theoretical point of view, the generation of this perpendicular magnetic anisotropy is closely related to factors such as interface effects, crystal structure and electronic state. For example, the crystal structure and chemical bonding mode at the interface between CoFeB and MgO play a key role in the induction of perpendicular magnetic anisotropy. Experimentally, through precise film deposition technology and annealing treatment, the structure and properties of the material can be adjusted to achieve and optimize perpendicular magnetic anisotropy. The perpendicular anisotropic structure of Ta / CoFeB / MgO film can significantly improve the storage density in MRAM, because the perpendicular magnetization allows the storage unit to be stacked in the vertical direction, and its good magnetoelectric properties can achieve high-speed reading and writing and low-power operation, which just meets the needs of storage technology for high-performance storage devices. In the field of spin electronics, using the spin properties of electrons instead of relying solely on charge for information processing and storage is the focus of research. The perpendicular anisotropy system of Ta / CoFeB / MgO thin films can provide a stable perpendicular magnetization source for spintronic devices, and can be used to construct spin logic devices, spin wave devices, etc. For example, in spin transfer torque (STT) devices, this perpendicular magnetization structure helps to reduce the critical current density and improve the efficiency of spin transfer torque, thereby promoting the development of spin electronics in a more practical direction.

[0004] The perpendicular magnetic anisotropic tunnel junction can effectively solve the disadvantages of the device needing to be designed as an ellipse or rectangle, low magnetization reversal efficiency and high power consumption. Through the successful development of the Ta / CoFeB / MgO / Ta interface perpendicular magnetic anisotropy (PMA) magnetic tunnel junction, since its thermal stability is determined by the magnetocrystalline anisotropy, this magnetic tunnel junction does not require a large aspect ratio to have high thermal stability and can be prepared into a cylindrical shape, which can further expand the process node of spin electronic devices to 20nm and below, laying the foundation for the realization of spin electronic information devices with smaller size and faster read and write speeds, which is of great significance for ultra-low power storage and computing. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a magnetron device for preparing a perpendicular magnetic anisotropic tunnel junction film and a preparation method thereof, which solves the problems mentioned in the background technology.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: a magnetron device prepares a perpendicular magnetic anisotropic tunnel junction thin film, including a silicon oxide wafer, a Ta film is deposited on the surface of the silicon oxide wafer, and the Ta film is used as a metal buffer layer, a CoFeB film is deposited on the surface of the Ta film, and the CoFeB film is used as a ferromagnetic layer, an MgO film is deposited on the surface of the CoFeB film, and the MgO film is used as an insulating layer to play the role of an insulating barrier, and a Ta film is also deposited on the surface of the MgO film, and the Ta film is used as a covering layer for anti-oxidation;

[0007] The Ta film, CoFeB film and MgO film are all produced by magnetron sputtering.

[0008] Preferably, the thickness of the Ta film is 3 nm, the thickness of the CoFeB film is t nm, and the thickness of the MgO film is 2 nm, wherein t is 0.9-1.4 nm.

[0009] The present invention also discloses a method for preparing a perpendicular magnetic anisotropic tunnel junction film using a magnetron device, which specifically comprises the following steps:

[0010] S1. Take a single-side polished silicon wafer with SiO2 on the surface, ultrasonically clean it in chemically pure acetone and ethanol for 10 minutes, then quickly blow dry it with nitrogen, and wait for standby;

[0011] S2. Start the magnetron equipment, and the operator places multiple wafers on the lifting multi-layer wafer bracket of the sample transfer room and starts the vacuum pump group;

[0012] S3. After waiting for the vacuum in the sample transfer chamber to reach the specified vacuum degree, open the transfer gate valve, and transfer the first wafer to the sample stage of the main chamber by lifting the multi-layer wafer holder and the automatic sample transfer arm. Close the transfer gate valve, and wait for the vacuum degree in the main chamber to reach the specified value. Then, send the wafer to the specified height of 35mm through the sample stage, and start to rotate at a constant speed of 80° / s. At the same time, introduce process gas argon. When the air pressure in the main chamber stabilizes at 0.36Pa, open the baffle of the Ta target in the cathode through the PC end, select the DC power supply, start the Ta target ignition, and then open the sample stage baffle. At the same time, start the timing of 10 minutes to deposit the Ta film. After sputtering, take out the deposited sample for roughness thickness test, and then calculate the sputtering rate of Ta.

[0013] S4. After waiting for the vacuum in the sample transfer chamber to reach the specified vacuum degree, open the transfer gate valve, and transfer the second wafer to the sample stage of the process main chamber by lifting the multi-layer wafer holder and the automatic sample transfer arm. Close the transfer gate valve, and wait for the vacuum degree in the main chamber to reach the specified value. Then, send the wafer to the specified height of 35mm through the sample stage, and start to rotate at a uniform speed of 80° / s. Introduce process gas argon. When the air pressure in the main chamber stabilizes at 0.34Pa, open the baffle of the CoFeB target in the cathode through the PC end, select the DC power supply, start the CoFeB target ignition, and then open the sample stage baffle. At the same time, start the timing of 10 minutes to deposit the CoFeB film. After sputtering, take out the deposited sample for roughness thickness test, and then calculate the CoFeB sputtering rate.

[0014] S5. After waiting for the vacuum in the sample transfer chamber to reach the specified vacuum degree, open the transfer gate valve, and transfer the third wafer to the sample stage of the process main chamber by lifting the multi-layer wafer holder and the automatic sample transfer arm. Close the transfer gate valve, and wait for the vacuum degree in the main chamber to reach the specified value. Then, send the wafer to the specified height of 35mm through the sample stage, and start to rotate at a uniform speed of 80° / s. Introduce process gas argon. When the main chamber is stabilized at 3Pa, open the baffle of the MgO target in the cathode through the PC end, select the RF power supply, start the MgO target ignition, and then set the opening of the electric pressure control valve to 44%. Wait for the pressure in the deposition chamber to stabilize at 0.2Pa, then open the sample stage baffle, and start the timing for 20 minutes to start depositing the MgO film. After sputtering, take out the deposited sample for roughness thickness test, and then calculate the sputtering rate of MgO.

[0015] S6. After waiting for the vacuum in the sample transfer chamber to reach the specified vacuum degree, open the transfer gate valve, and transfer the fourth wafer to the sample table of the main chamber by lifting the multilayer wafer holder and the automatic sample transfer arm, close the transfer gate valve, and then prepare the magnetic tunnel junction multilayer film with perpendicular magnetic anisotropy of Ta 3nm / CoFeB 2nm / MgO 2nm / Ta3nm interface according to the experimental processes of the above steps S3, S4 and S5, and the calculated sputtering rates of Ta, CoFeB and MgO.

[0016] Preferably, in step S3 and step S4, the DC power supply power is set to 50 W, and the sputtering time is set to 10 minutes. In step S5, the RF power supply power is set to 80 W, and the sputtering time is set to 20 minutes.

[0017] Preferably, in both step S3 and step S4, the gas flow rate is set to 4 sccm through the PC end, and in step S5, the gas flow rate is set to 15 sccm through the PC end.

[0018] Preferably, the opening degree of the electric pressure control valve in step S3 and step S4 is 30%.

[0019] Preferably, in step S5, the opening of the electric pressure control valve is first adjusted to 5%, and then the electric pressure control valve is opened to 44% after the MgO target is ignited.

[0020] Preferably, the magnetron device comprises a main chamber and a sample transfer chamber, and a transfer gate valve is arranged inside the sample transfer chamber, a sample table is arranged above the main chamber, a lifting multi-layer wafer holder is arranged below the sample transfer chamber, and an automatic sample transfer arm is arranged on one side of the sample transfer chamber.

[0021] Preferably, a cathode is disposed below the main chamber, and three cathodes are disposed, and a Ta target, a CoFeB target and a MgO target are disposed at one end of the three cathodes, respectively.

[0022] Preferably, an electric pressure control valve is provided at the rear of the main chamber.

[0023] Beneficial Effects

[0024] The present invention provides a magnetron device for preparing a perpendicular magnetic anisotropic tunnel junction thin film and a preparation method thereof, which has the following beneficial effects compared with the prior art:

[0025] (1) The magnetron device prepares perpendicular magnetic anisotropic tunnel junction thin films and the preparation method thereof, and reduces the surface roughness of Ta, CoFeB, and MgO thin films by adjusting experimental parameters such as process gas pressure, sputtering power, and sputtering distance.

[0026] (2) The magnetron device prepares a perpendicular magnetic anisotropic tunnel junction film and its preparation method, and improves the crystallization of MgO by reducing the process gas pressure, increasing the sputtering power and other experimental parameters.

[0027] (3) The magnetron device is used to prepare perpendicular magnetic anisotropic tunnel junction films and their preparation methods. By using high-precision magnetron equipment and adjusting experimental parameters such as process gas pressure, sputtering power, and sputtering distance, precise deposition of CoFeB films with a thickness of 0.1 nm is achieved.

[0028] (4) The magnetron device prepares a perpendicular magnetic anisotropic tunnel junction film and a preparation method thereof. According to the structure of a 3nm thick Ta film, a 1.4nm thick CoFeB film, a 2nm thick MgO film, and a 3nm thick Ta film, a magnetic tunnel junction multilayer film with excellent PMA signals can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the thickness of the Ta film in 10 minutes of the present invention;

[0030] Figure 2 It is a schematic diagram of the roughness of the Ta film of the present invention after 10 minutes;

[0031] Figure 3 It is a schematic diagram of the thickness of the CoFeB film in 10 minutes of the present invention;

[0032] Figure 4 It is a schematic diagram of the roughness of the CoFeB film of the present invention after 10 minutes;

[0033] Figure 5 It is a schematic diagram of the thickness of the MgO film at 20 minutes of the present invention;

[0034] Figure 6 It is a schematic diagram of the roughness of the MgO film of the present invention after 20 minutes;

[0035] Figure 7 It is a film layer stacking diagram of the present invention;

[0036] Figure 8 This is the MOKE image of the present invention when t is 1.3 nm;

[0037] Fig. 9 This is the MOKE image of the present invention when t is 1.4 nm;

[0038] Fig.10 It is a structural schematic diagram of the magnetron device of the present invention.

[0039] In the figure: 1. Main chamber; 2. Sample transfer chamber; 3. Sample stage; 4. Cathode; 5. Automatic sample transfer arm; 6. Electric pressure control valve; 7. Transfer gate valve; 8. Lifting multi-layer wafer holder. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Embodiment 1

[0042] See also Figures 1 to 10 As shown, the present invention provides a technical solution, and the specific improvements are as follows:

[0043] A magnetron device is used to prepare a perpendicular magnetic anisotropic tunnel junction thin film, comprising a silicon oxide wafer, a Ta film is deposited on the surface of the silicon oxide wafer, the Ta film is used as a metal buffer layer, a CoFeB film is deposited on the surface of the Ta film, the CoFeB film is used as a ferromagnetic layer, an MgO film is deposited on the surface of the CoFeB film, the MgO film is used as an insulating layer to act as an insulating barrier, and a Ta film is also deposited on the surface of the MgO film, the Ta film is used as a covering layer for oxidation prevention, the thickness of the Ta film is 3nm, the thickness of the CoFeB film is 0.9nm, and the thickness of the MgO film is 2nm;

[0044] The Ta film, CoFeB film and MgO film are all produced by magnetron sputtering.

[0045] Embodiment 2

[0046] Based on Example 1, please refer to Figures 1 to 10 The specific improvements are as follows:

[0047] The present invention also discloses a method for preparing a perpendicular magnetic anisotropic tunnel junction film using a magnetron device, which specifically comprises the following steps:

[0048] S1. Take a single-side polished silicon wafer with SiO2 on the surface, ultrasonically clean it in chemically pure acetone and ethanol for 10 minutes, then quickly blow dry it with nitrogen, and wait for standby;

[0049] S2, start the magnetron device, the operator puts multiple wafers on the lifting multi-layer wafer bracket 8 of the sample transfer chamber 2, and starts the vacuum pump group;

[0050] S3, after waiting for the vacuum of the sample transfer chamber 2 to reach the specified vacuum degree, open the transfer gate valve 7, and send the first wafer to the sample stage 3 of the main chamber 1 by lifting the multilayer wafer holder 8 and the automatic sample transfer arm 5, close the transfer gate valve 7, wait for the vacuum degree in the main chamber 1 to reach the specified value, send the wafer to the specified height of 35mm through the sample stage 3, and start to rotate at a uniform speed of 80° / s, introduce process gas argon, set the gas flow rate to 4sccm through the PC end, set the opening of the electric pressure control valve 6 to 30%, wait for the main chamber 1 to stabilize at 0.36Pa, open the baffle of the Ta target in the cathode 4 through the PC end, select the DC power supply, set the DC power supply power to 50W, start the Ta target ignition, set the sputtering time to 10 minutes, open the baffle of the sample stage 3, start to deposit the Ta film, take out the deposited sample after sputtering, and perform AFM characterization on the prepared Ta film, such as Figure 1 and 2 As shown, the thickness of the Ta film deposited in 10 minutes is 18.540nm, and the roughness Ra is 0.197nm. The excellent roughness meets the initial requirements for preparing PMA;

[0051] S4, after waiting for the vacuum of the sample transfer chamber 2 to reach the specified vacuum degree, open the transfer gate valve 7, and send the second wafer to the sample stage 3 of the process main chamber 1 by lifting the multi-layer wafer holder 8 and the automatic sample transfer hand 5, close the transfer gate valve 7, wait for the vacuum degree in the main chamber 1 to reach the specified value, send the wafer to the specified height of 35mm through the sample stage 3, and start to rotate at a uniform speed of 80° / s, introduce process gas argon, set the gas flow rate to 4sccm through the PC end, set the opening of the electric pressure control valve 6 to 30%, wait for the main chamber 1 to stabilize at 0.34Pa, open the baffle of the 4CoFeB target in the cathode 4 through the PC end, select the DC power supply, set the DC power supply power to 50W, start the CoFeB target ignition, set 10 minutes in the timing device, and open the baffle of the sample stage 3 at the same time, start to deposit the CoFeB film, and perform AFM characterization on the prepared CoFeB film, such as Figure 3 and 4 As shown, the thickness of the Ta film deposited in 10 minutes is 11.424nm, and the roughness Ra is 0.397nm. The excellent roughness meets the initial requirements for preparing PMA;

[0052] S5, after waiting for the vacuum of the sample transfer chamber 2 to reach the specified vacuum degree, open the transfer gate valve 7, and send the third wafer to the sample stage 3 of the process main chamber 1 by lifting the multi-layer wafer holder 8 and the automatic sample transfer hand 5, close the transfer gate valve 7, wait for the vacuum degree in the main chamber 1 to reach the specified value, send the wafer to the specified height of 35mm through the sample stage 3, and start to rotate at a uniform speed of 80° / s, introduce process gas argon, set the gas flow rate to 15sccm through the PC end, set the opening of the electric pressure control valve 6 to 5%, wait for the main chamber 1 to stabilize at 3Pa, open the baffle of the MgO target in the cathode 4 through the PC end, select the RF power supply, set the RF power supply power to 80W, start the MgO target ignition, and then set the opening of the electric pressure control valve 6 to 44%, wait for the deposition chamber pressure to stabilize at 0.2Pa, set 20 minutes in the timing device, and open the baffle of the sample stage 3 at the same time to start the deposition of MgO film, and perform AFM characterization on the prepared MgO film, such as Figure 5 and 6 As shown, after 20 minutes, the thickness of the deposited MgO layer is 3.080 nm, and the roughness Ra is 0.182 nm. The excellent roughness meets the preliminary requirements for preparing PMA.

[0053] S6. After waiting for the vacuum of the sample transfer chamber 2 to reach the specified vacuum degree, open the transfer gate valve 7, and transfer the fourth wafer to the sample stage 3 of the main chamber 1 by lifting the multilayer wafer holder 8 and the automatic sample transfer arm 5, close the transfer gate valve 7, and then prepare the magnetic tunnel junction multilayer film with perpendicular magnetic anisotropy of Ta 3nm / CoFeB t nm / MgO2nm / Ta 3nm interface according to the experimental processes of the above steps S3, S4 and S5, and the calculated sputtering rates of Ta, CoFeB and MgO.

[0054] Embodiment 3

[0055] The specific difference between this embodiment and the second embodiment is that the thickness of the CoFeB film is 1.1 nm.

[0056] Embodiment 4

[0057] The specific difference between this embodiment and the second embodiment is that the thickness of the CoFeB film is 1.3 nm.

[0058] Embodiment 5

[0059] Compared with the second embodiment, the specific differences of this embodiment are: the thickness of the CoFeB film is 1.4 nm;

[0060] Four groups of samples were prepared with CoFeB films of 0.9nm, 1.1nm, 1.3nm and 1.4nm thickness, and the magneto-optical Kerr measurement system MOKE test was performed on the four groups of Ta / CoFeB / MgO / Ta multilayer films. The results are shown in the figure. Figure 8 and 9 As shown, when the CoFeB film is 1.3nm and 1.4nm, excellent PMA signals are measured, and it is found through observation that when the CoFeB film is 1.4nm, the PMA signal of the magnetic tunnel junction multilayer film of the perpendicular magnetic anisotropy PMA of the Ta / CoFeB / MgO / Ta interface is the best.

[0061] Embodiment 6

[0062] Based on the second embodiment, please refer to the following, the specific improvements are as follows:

[0063] The magnetron device comprises a main chamber 1, a sample transfer chamber 2 and a molecular pump, and a transmission gate valve 7 is arranged inside the sample transfer chamber 2, and the connection and isolation with the sample transfer chamber 2 are realized by the transmission gate valve 7. A sample stage 3 is arranged above the main chamber 1, and a lifting multi-layer wafer holder 8 is arranged below the sample transfer chamber 2. An automatic sample transfer hand 5 is arranged on one side of the sample transfer chamber 2, and the wafer is transported from the sample transfer chamber 2 to the sample stage 3 by lifting the multi-layer wafer holder 8 and the automatic sample transfer hand 5. A cathode 4 is arranged below the main chamber 1, and three cathodes 4 are arranged, and one end of the three cathodes 4 is respectively arranged with a Ta target, a CoFeB target and a MgO target. An electric pressure control valve 6 is arranged at the rear of the main chamber 1, and is connected to the molecular pump through the electric pressure control valve 6 to realize upstream or downstream pressure control.

[0064] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0065] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A magnetron device is used to prepare a perpendicular magnetic anisotropic tunnel junction film, characterized in that: It comprises a silicon oxide wafer, a Ta film is deposited on the surface of the silicon oxide wafer, the Ta film is used as a metal buffer layer, a CoFeB film is deposited on the surface of the Ta film, the CoFeB film is used as a ferromagnetic layer, an MgO film is deposited on the surface of the CoFeB film, the MgO film is used as an insulating layer to act as an insulating barrier, and a Ta film is also deposited on the surface of the MgO film, the Ta film is used as a covering layer for anti-oxidation; The Ta film, CoFeB film and MgO film are all prepared by magnetron sputtering.

2. A magnetron device is used to prepare a perpendicular magnetic anisotropic tunnel junction film, characterized in that: The thickness of the Ta film is 3 nm, the thickness of the CoFeB film is t nm, and the thickness of the MgO film is 2 nm, wherein t is 0.9-1.4 nm.

3. A method for preparing a perpendicular magnetic anisotropic tunnel junction film using a magnetron device, characterized in that: The specific steps include: S1. Take a single-side polished silicon wafer with SiO2 on the surface, ultrasonically clean it in chemically pure acetone and ethanol for 10 minutes, then quickly blow dry it with nitrogen, and wait for standby use; S2, starting the magnetron device, the operator places a plurality of wafers on the lifting multi-layer wafer bracket (8) of the sample transfer chamber (2), and starts the vacuum pump group; S3, after waiting for the vacuum of the sample transfer chamber (2) to reach the specified vacuum degree, open the transfer gate valve (7), and carry the first wafer to the sample stage (3) of the main chamber (1) by lifting the multi-layer wafer holder (8) and the automatic sample transfer arm (5), close the transfer gate valve (7), wait for the vacuum degree in the main chamber (1) to reach the specified value, and then carry the wafer to the specified height of 35mm through the sample stage (3), and start to rotate at a constant speed of 80° / s, while introducing the process gas argon, wait until the air pressure in the main chamber (1) stabilizes at 0.36Pa, open the baffle of the Ta target in the cathode (4) through the PC end, select the DC power supply, start the Ta target ignition, and then open the baffle of the sample stage (3), and start the timing of 10 minutes to deposit the Ta film. After sputtering is completed, take out the deposited sample for roughness thickness test, and then calculate the sputtering rate of Ta; S4, after waiting for the vacuum of the sample transfer chamber (2) to reach the specified vacuum degree, open the transfer gate valve (7), and carry the second wafer to the sample stage (3) of the process main chamber (1) by lifting the multi-layer wafer holder (8) and the automatic sample transfer arm (5), close the transfer gate valve (7), wait for the vacuum degree in the main chamber (1) to reach the specified value, and then carry the wafer to the specified height of 35mm through the sample stage (3), and start to rotate at a constant speed of 80° / s, introduce process gas argon, and wait until the air pressure in the main chamber (1) stabilizes at 0.34Pa, open the baffle of the CoFeB target in the cathode (4) through the PC end, select the DC power supply, start the CoFeB target ignition, and then open the baffle of the sample stage (3), and start the timing of 10 minutes to deposit the CoFeB film. After sputtering is completed, take out the deposited sample for roughness thickness test, and then calculate the CoFeB sputtering rate; S5, after waiting for the vacuum of the sample transfer chamber (2) to reach the specified vacuum degree, open the transfer gate valve (7), and transfer the third wafer to the sample stage (3) of the process main chamber (1) by lifting the multi-layer wafer holder (8) and the automatic sample transfer arm (5), close the transfer gate valve (7), wait for the vacuum degree in the main chamber (1) to reach the specified value, send the wafer to the specified height of 35mm through the sample stage (3), and start to rotate at a constant speed of 80° / s, introduce process gas argon, wait for the main chamber (1) to stabilize at 3Pa, open the baffle of the MgO target in the cathode (4) through the PC end, select the radio frequency power supply, start the MgO target ignition, and then set the opening of the electric pressure control valve (6) to 44%, wait for the deposition chamber pressure to stabilize at 0.2Pa, then open the baffle of the sample stage (3), and start the timing of 20 minutes to start the deposition of the MgO film. After the sputtering is completed, take out the deposited sample for roughness thickness test, and then calculate the sputtering rate of MgO; S6. After the vacuum of the sample transfer chamber (2) reaches a specified vacuum degree, the transfer gate valve (7) is opened, and the fourth wafer is transferred to the sample stage (3) of the main chamber (1) by lifting the multilayer wafer holder (8) and the automatic sample transfer arm (5), and the transfer gate valve (7) is closed. Then, according to the experimental processes of the above steps S3, S4 and S5, and the calculated sputtering rates of Ta, CoFeB and MgO, a magnetic tunnel junction multilayer film with perpendicular magnetic anisotropy of Ta 3nm / CoFeB 2nm / MgO 2nm / Ta 3nm interface is prepared.

4. The method for preparing a perpendicular magnetic anisotropic tunnel junction thin film by a magnetron device according to claim 3, characterized in that: In the step S3 and the step S4, the DC power supply power is set to 50 W, and the sputtering time is set to 10 minutes. In the step S5, the RF power supply power is set to 80 W, and the sputtering time is set to 20 minutes.

5. The method for preparing a perpendicular magnetic anisotropic tunnel junction thin film by a magnetron device according to claim 4, characterized in that: In both step S3 and step S4, the gas flow rate is set to 4 sccm through the PC end, and in step S5, the gas flow rate is set to 15 sccm through the PC end.

6. The method for preparing a perpendicular magnetic anisotropic tunnel junction thin film by a magnetron device according to claim 5, characterized in that: In the steps S3 and S4, the opening degree of the electric pressure control valve (6) is 30%.

7. The method for preparing a perpendicular magnetic anisotropic tunnel junction thin film by a magnetron device according to claim 6, characterized in that: In the step S5, the opening of the electric pressure control valve (6) is first adjusted to 5%, and after the MgO target is ignited, the electric pressure control valve (6) is opened to 44%.

8. The method for preparing a perpendicular magnetic anisotropic tunnel junction thin film by a magnetron device according to claim 7, characterized in that: The magnetron device comprises a main chamber (1) and a sample transfer chamber (2), wherein a transfer gate valve (7) is arranged inside the sample transfer chamber (2), a sample stage (3) is arranged above the main chamber (1), a lifting multi-layer wafer holder (8) is arranged below the sample transfer chamber (2), and an automatic sample transfer arm (5) is arranged on one side of the sample transfer chamber (2).

9. The method for preparing a perpendicular magnetic anisotropic tunnel junction thin film by a magnetron device according to claim 8, characterized in that: A cathode (4) is arranged below the main chamber (1), three cathodes (4) are arranged, and one end of the three cathodes (4) is respectively arranged with a Ta target, a CoFeB target and a MgO target.

10. The method for preparing a perpendicular magnetic anisotropic tunnel junction thin film by a magnetron device according to claim 9, characterized in that: An electric pressure control valve (6) is arranged at the rear of the main chamber (1).